NILAI-NILAI KEPRIBADIAN TOKOH UTAMA DALAM KUMPULAN CERPEN YULI S’LALU SMART DI MEDIA SOSIAL FACEBOOK KARYA YULISMAR - Viny Peprionita; Syafrial Syafrial; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research entitled the personality of the main character in the collection of short stories Yuli s'lalu smart in social media facebook by Yulismar. The purpose of this study is to describe the values of positive personality and negative personality values of the main character in the collection of short stories Yuli s'lalu smart in social media facebook by Yulismar. The result of the research of positive personality values of the main characters in the collection of short stories that have been studied amounted to 56 data, and the negative personality values of the main characters amounted to 8 data. The total data is 64 data. The values of the main character personality in the collection of short stories that have been studied was more dominant to the positive personality. Positive personalities that tend to appear that is a religious personality. The revealed religious personality amounted to 27 data.Keywords: Values, Personality, The Main Character ,Short Story